2009
DOI: 10.1143/jjap.48.071204
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Behaviors of Phonon-Limited Electron Mobility of Sub-10-nm-Thick Silicon-on-Insulator Metal–Oxide–Semiconductor Field-Effect Transistor with (001) and (111) Si Surface Channels

Abstract: In this study we simulate the impact of silicon layer thickness and temperature on the phonon-limited electron mobility of the inversion layer for ultrathin-body ( 111) and ( 001) surface silicon-on-insulator (SOI) layers in single-gate (SG) and double-gate (DG) SOI metal-oxidesemiconductor field-effect transistors (MOSFETs); one-dimensional self-consistent calculations and relaxation time approximations are performed. For a sub-10-nm-thick SOI layer, it is demonstrated that intra-subband phonon scattering at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, the phonon scattering mobility (µ ph ), coulomb mobility (µ coul ) and surface roughness mobility (µ sr ) on the (100)/<110> Si surfaces were also calculated through our solver. To consider the physical mechanism of mobility enhancement in strained nMOSFETs, we take the intravalley and intervalley phonon scattering into account [6,8]. The traditional theory of intravalley and intervalley phonon scattering has already been developed and expressions for the momentum relaxation rate have been obtained.…”
Section: Mobility Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the phonon scattering mobility (µ ph ), coulomb mobility (µ coul ) and surface roughness mobility (µ sr ) on the (100)/<110> Si surfaces were also calculated through our solver. To consider the physical mechanism of mobility enhancement in strained nMOSFETs, we take the intravalley and intervalley phonon scattering into account [6,8]. The traditional theory of intravalley and intervalley phonon scattering has already been developed and expressions for the momentum relaxation rate have been obtained.…”
Section: Mobility Simulationmentioning
confidence: 99%
“…The strain changes the electronic band structure resulting in the change of carrier mobility [1][2][3][4][5]. While the electrostatics of strained MOSFETs has been studied, several research groups have reported the mobility characteristic in strained MOSFETs [1,6] or in unstrained MOSFETs [7,8]. It is also reported that the intervalley phonon scattering is required to accurately explain the behavior of inversion layer mobility in both strained and unstrained Si MOSFETs [9].…”
Section: Introductionmentioning
confidence: 99%